Implications of Political Trust, Kinship Politics, and Political Participation (Makassar City Election in 2020) - Bakar, Dadang Mas; Hidayat, Eri Radityawara; Malik, Ihsan (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
Several previous studies on political participation prove that trust is an essential variable in increasing individual political participation. Besides that, Kinship politics make community participation decline. This study aims to see the implications of political trust in increasing public participation in the implementation of the 2020 regional elections simultaneously in Makassar City and how the political kinship implications are with the other two variables. In this research, a literature study approach is used by taking data on political trust and political participation and supporting theories that can reveal the implications of these two variables. The entire data found was then analyzed, which was connected to the situation in Makassar City in 2020. This research focuses on the regional elections held in Makassar City in 2020 due to the 2018 regional elections, won by empty boxes. This study found that the level of trust and political participation in Makassar city is very similar, proving the implications of these two variables. Then, several things can influence trust to increase political participation, namely kinship politics, security, and political knowledge through political education. This study also provides several recommendations for activities that can be carried out to increase political participation through a political trust approach.